2019
DOI: 10.1039/c9en00222g
|View full text |Cite
|
Sign up to set email alerts
|

Surface-controlled dissolution rates: a case study of nanoceria in carboxylic acid solutions

Abstract: Nanoparticle dissolution in local milieu can affect their ecotoxicity and therapeutic applications. For example, carboxylic acid release from plant roots can solubilize nanoceria in the rhizosphere, affecting cerium uptake in plants. Nanoparticle dispersions were dialyzed against ten carboxylic acid solutions for up to 30 weeks; the membrane passed cerium-ligand complexes but not nanoceria. Dispersion and solution samples were analyzed for cerium by inductively coupled plasma mass spectrometry (ICP-MS). Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
(100 reference statements)
3
17
0
Order By: Relevance
“…The cerium concentration in the bath of the dialysis system that contained solvothermally synthesized nanoceria in the cassette increased over time, indicating nanoceria dissolution. Citric and lactic acid increased the dissolution rate (Table 2), as previously reported [39,40]. The rate of NM-212 dissolution was much slower (Figure 8 and Table 2).…”
Section: Nanoceria Dissolutionsupporting
confidence: 83%
See 3 more Smart Citations
“…The cerium concentration in the bath of the dialysis system that contained solvothermally synthesized nanoceria in the cassette increased over time, indicating nanoceria dissolution. Citric and lactic acid increased the dissolution rate (Table 2), as previously reported [39,40]. The rate of NM-212 dissolution was much slower (Figure 8 and Table 2).…”
Section: Nanoceria Dissolutionsupporting
confidence: 83%
“…The cassette contained 500 μg cerium (as solvothermally synthesized nanoceria in 1 mL). In an initial experiment, samples were withdrawn from duplicate cassettes five times from 1344 to 4704 h. The cerium concentration in the cassettes decreased much faster at pH 4.5 than at pH 7.4, consistent with prior results [39,40]. The experiment was repeated with additional duplicate systems containing no LN resin at pH 4.5 and no HTP at pH 7.4.…”
Section: Nanoceria Dissolution In the Presence Of Immobilized Phosphatessupporting
confidence: 69%
See 2 more Smart Citations
“…Some authors have reported the observation of dissolution phenomena on colloidal dispersions of nanoparticles subjected to thermal treatments. 10,[70][71][72][73][74][75] However, in the case of core-shell nanoparticles, the dependence of the dissolution phenomena on the size and the chemical nature of the shell has not been treated so far. Here, the systematic study revealed that manganese dissolution is more evident with shells formed by iron oxide rather than cobalt ferrite.…”
Section: Mna-based Core-shell Nanoparticlesmentioning
confidence: 99%